Present Status of Chemicals and Aqua Drugs Used in The Freshwater Fish Health Management of Kurigram District in Bangladesh (Research in Agriculture Livestock and Fisheries, 2025)
A survey was conducted to assess the current status of aqua-drugs and chemicals used in freshwater aquaculture practices in Kurigram district, Bangladesh. Data were collected through random sampling using participatory rural appraisal (PRA) tools, including structured questionnaires, personal interviews, market surveys, and focus group discussions (FGDs), involving fish hatchery owners, nursery and grow-out farmers, aqua-medicine retailers, and representatives of pharmaceutical companies. The results revealed that farmers had varying levels of experience and training, with limited access to formal training opportunities. Major water quality problems reported included dissolved oxygen (DO) deficiency (94%), gaseous problems (54%), poor phytoplankton availability (33%), turbidity (32%), algal blooms (19%), and pH imbalance (11%). Common fish diseases observed were fin rot (48%), tail rot (47%), epizootic ulcerative syndrome (EUS) (31%), argulosis (25%), exophthalmia (24%), dropsy (23%), and gill rot (17%). To mitigate these problems, farmers commonly applied various aqua-drugs and chemicals, such as zeolite (43%), Matrix (18%), Zeorich (13%), and Green Cal Aqua (7%) for pond preparation and fish health management, while potash (41%), Timsen (22%), lime (14%), and Virex (12%) were frequently used for disease treatment. The study also identified significant challenges related to the inappropriate and indiscriminate use of these chemicals, primarily due to farmers’ limited knowledge regarding proper dosages, application methods, and potential impacts. The findings highlight the need for improved training and awareness programs and are expected to support fish farmers in adopting appropriate chemical use for healthier and more sustainable aquaculture practices.Res. Agric. Livest. Fish. Vol. 12, No. 3, December 2025: 517-527